Coagulopathy and COVID-19. (8th October 2021) - Lorini, Ferdinando Luca; Di Matteo, Maria; Gritti, Paolo; Grazioli, Lorenzo; Benigni, Alberto; Zacchetti, Lucia; Bianchi, Isabella; Fabretti, Fabrizio; Longhi, Luca
Abstract: SARS-CoV-2 infection is associated with frequent thrombotic events, at the micro and macro-vascular level, due to the perpetuation of a state of hypercoagulability. The so-called 'COVID-19 associated coagulopathy' (CAC) represents a key aspect in the genesis of organ damage from SARS-CoV-2. The main coagulative alterations described in the literature are represented by high levels of D-dimer and fibrinogen. Although CAC has some common features with disseminated intravascular coagulation and sepsis-induced coagulopathy, there are important differences between these clinical pictures and the phenotype of CAC is unique. The pathogenesis of CAC is complex and is affected by the strong interconnection between the inflammatory system and coagulation, in the phenomenon of immunothrombosis and thrombo-inflammation. Several mechanisms come into play, such as inflammatory cytokines, neutrophils, the complement system as well as an alteration of the fibrinolytic system. Finally, an altered platelet function and especially endothelial dysfunction also play a central role in the pathophysiology of CAC. Heparin has several potential effects in CAC, in fact in addition to the anticoagulant effect, it could have a direct antiviral effect and anti-inflammatory properties. The high incidence of thrombo-embolic phenomena despite the use of antithrombotic prophylaxis have led some experts to recommend the use of anticoagulant doses of heparin, but at present the optimal anticoagulant regimen remains to be determined.